Mapping the interactions between the NS4B and NS3 proteins of dengue virus - Zou, Jing (2015)
Flavivirus RNA synthesis is mediated by a multiprotein complex associated with the endoplasmic reticulum membrane, named the replication complex (RC). Within the flavivirus RC, NS4B, an integral membrane protein with a role in virulence and regulation of the innate immune response, binds to the NS3 protease-helicase. NS4B modulates the RNA helicase activity of NS3, but the molecular details of their interaction remain elusive. Here, we used dengue virus (DENV) to map the determinants for the NS3-NS4B interaction. Coimmunoprecipitation and an in situ proximity ligation assay confirmed that NS3 colocalizes with NS4B in both DENV-infected cells and cells coexpressing both proteins. Surface plasmon resonance demonstrated that subdomains 2 and 3 of the NS3 helicase region and the cytoplasmic loop of NS4B are required for binding. Using nuclear magnetic resonance (NMR), we found that the isolated cytoplasmic loop of NS4B is flexible, with a tendency to form a three-turn α-helix and two short β-strands. Upon binding to the NS3 helicase, 12 amino acids within the cytoplasmic loop of NS4B exhibited line broadening, suggesting a participation in the interaction. Sequence alignment showed that 4 of these 12 residues are strictly conserved across different flaviviruses. Mutagenesis analysis showed that three (Q134, G140, and N144) of the four evolutionarily conserved NS4B residues are essential for DENV replication. The mapping of the NS3/NS4B-interacting regions described here can assist the design of inhibitors that disrupt their interface for antiviral therapy. IMPORTANCE: NS3 and NS4B are essential components of the flavivirus RC. Using DENV as a model, we mapped the interaction between the viral NS3 and NS4B proteins. The subdomains 2 and 3 of NS3 helicase as well as the cytoplasmic loop of NS4B are critical for the interaction. Functional analysis delineated residues within the NS4B cytoplasmic loop that are crucial for DENV replication. Our findings reveal molecular details of how flavivirus NS3 protein cooperates with NS4B within the RC. In addition, this study has established the rationale and assays to search for inhibitors disrupting the NS3-NS4B interaction for antiviral drug discovery.